The greatest challenges and solutions to improve children's health and well-being worldwide in the next decade and beyond: Using complex systems and implementation science approaches - Tyack, Zephanie (Frontiers in Pediatrics, 2023)
The health and wellbeing of children is paramount to health and wellbeing of society and is the foundation of health and wellbeing later in life. This paper presents the perspective that a complex systems approach that embeds implementation science is needed to address the rising challenges to child health and wellbeing in the next decade and beyond. Reflection on the facilitators of the success of programs deemed promising to address child health and wellbeing in the last decade is presented, to advance programs to address children’s health and well-being in the next decade. A priority that needs to be addressed is developing, testing and using fully developed theories of child health and well-being that can be used to build on existing successes to make progress. Further elucidating the drivers of child health and well-being at multiple levels of the health system extending across the life course and understanding contexts also requires greater consideration in the next decade. Methods to address future challenges to child health and wellbeing include co-designing models of child health and wellbeing with children and families themselves rather than using predesigned interventions, thoughtful outcome selection, and reporting the challenges of implementing future programs to promote learning. The approaches, priorities and methods presented can be used to design interventions, models or care or community-based initiatives and provide new direction to fields of child health enquiry.